Communities at the Crossroads: Forest or large-scale monoculture in Kalimantan, Indonesia - Yuliani, E.L. (Radboud University, 2022)
The forests of Indonesia are home to globally important biodiversity, perform many ecosystem services on the regional scale and are a source of livelihoods for thousands of local communities, and at the heart of culture and traditional knowledge systems. The forest has also become a battleground where powerful actors of land use change meet with communities who struggle to restore traditional communal rights over natural resources and land. By and large in this process, the forest is disappearing, mostly replaced by large scale agro-development projects. Inspired by the desire to contribute to better protection of forest, local culture and traditional knowledge systems, this thesis is aimed to gain an in-depth understanding of what happens when powerful corporations lay claim to natural resources inhabited by indigenous people, which is a worldwide phenomenon.